A critical review of resource recovery from municipal wastewater treatment plants – market supply potentials, technologies and bottlenecks. Issue 4 (21st January 2020) - Kehrein, Philipp; van Loosdrecht, Mark; Osseweijer, Patricia; Garfí, Marianna; Dewulf, Jo; Posada, John
Abstract : This critical review reveals the technologies and potentials to recover water, energy, fertilizers and products from municipal WWTPs but also analyses the various bottlenecks that may their hinder successful implementation. Abstract : In recent decades, academia has elaborated a wide range of technological solutions to recover water, energy, fertiliser and other products from municipal wastewater treatment plants. Drivers for this work range from low resource recovery potential and cost effectiveness, to the high energy demands and large environmental footprints of current treatment-plant designs. However, only a few technologies have been implemented and a shift from wastewater treatment plants towards water resource facilities still seems far away. This critical review aims to inform decision-makers in water management utilities about the vast technical possibilities and market supply potentials, as well as the bottlenecks, related to the design or redesign of a municipal wastewater treatment process from a resource recovery perspective. Information and data have been extracted from literature to provide a holistic overview of this growing research field. First, reviewed data is used to calculate the potential of 11 resources recoverable from municipal wastewater treatment plants to supply national resource consumption. Depending on the resource, the supply potential may vary greatly. Second, resource recovery technologies investigated in academia are reviewed comprehensively and critically. The third section of the review identifies nine non-technical bottlenecks mentioned in literature that have to be overcome to successfully implement these technologies into wastewater treatment process designs. The bottlenecks are related to economics and value chain development, environment and health, and society and policy issues. Considering market potentials, technological innovations, and addressing potential bottlenecks early in the planning and process design phase, may facilitate the design and integration of water resource facilities and contribute to more circular urban water management practices.